Synthesis and Characterization of 5- and 6- Coordinated Alkali Pertechnetates. (12th January 2017) - Weaver, Jamie; Soderquist, Chuck; Gassman, Paul; Walter, Eric; Lukens, Wayne; McCloy, John S.
ABSTRACT: The local chemistry of technetium-99 ( 99 Tc) in oxide glasses is important for understanding the incorporation and long-term release of Tc from nuclear waste glasses, both those for legacy defense wastes and fuel reprocessing wastes. Tc preferably forms Tc(VII), Tc(IV), or Tc(0) in glass, depending on the level of reduction of the melt. Tc(VII) in oxide glasses is normally assumed to be isolated pertechnetate TcO4 - anions surrounded by alkali, but can occasionally precipitate as alkali pertechnetate salts such as KTcO4 and NaTcO4 when Tc concentration is high. In these cases, Tc(VII) is 4-coordinated by oxygen. A reinvestigation of the chemistry of alkali-technetium-oxides formed under oxidizing conditions and at temperatures used to prepare nuclear waste glasses showed that higher coordinated alkali Tc(VII) oxide species had been reported, including those with the TcO5 - and TcO6 - anions. The chemistry of alkali Tc(VII) and other alkali-Tc-oxides is reviewed, along with relevant synthesis conditions. Additionally, we report attempts to make 5- and 6-coordinate pertechnetate compounds of K, Na, and Li, i.e. TcO5 - and TcO6 - . It was found that higher coordinated species are very sensitive to water, and easily decompose into their respective pertechnetates. It was difficult to obtain pure compounds, but mixtures of the pertechnetate and other phase(s) were frequently found, as evidenced by x-ray absorption spectroscopy (XAS), neutron diffraction (ND), and Raman spectroscopy. Low temperature electron paramagnetic resonance (EPR) measurements showed the possibility of Tc(IV) and Tc(VI) in Na3 TcO5 and Na5 TcO6 compounds. It was hypothesized that the smaller counter cation would result in more stable pertechnetates. To confirm the synthesis method, LiReO4 and Li5 ReO6 were prepared, and their Raman spectra match those in the literature. Subsequently, the Tc versions LiTcO4 and Li5 TcO6 were synthesized and characterized by ND, Raman spectroscopy, XANES, and EXAFS. The Li5 TcO6 was a marginally stable compound that appears to have the same structure as that known for Li5 ReO6 . Implications of the experimental work on stability of alkali technetate compounds and possible role in the volatilization of Tc are discussed.